Розвиток підприємства в умовах формування інклюзивної економічної моделі - Батіг, В. В. (ХНУРЕ, 2025)
Recently, inclusion has been actively promoted in various spheres of public economic life. In a general sense, inclusiveness is the involvement of all people in socially active life, regardless of their physical, material, financial or other capabilities. Business management in the areas of inclusion is responsible for ensuring the employment of such individuals. Economies on the principles of inclusion are responsible for conducting business as much as the average company. However, the principles of responsibility are at the core of the management of great corporations.
Keywords: розвиток підприємства; інклюзивна економічна модель